Predominance of two M-types among erythromycin-resistant group A Streptococci from Greek children. - Zachariadou, L; J Papaparaskevas; Paraskakis, I; Efstratiou, A; Pangalis, A; Legakis, N J; Tassios, P T (Clin Microbiol Infect, 2003)
In order to investigate the potential relationship between erythromycin resistance and specific M-serotypes among clinical isolates of Streptococcus pyogenes from children in Greece, we randomly selected a total of 49 erythromycin-resistant (EryR) and 21 erythromycin-susceptible (EryS) isolates from the 1158 S. pyogenes isolates from the two main children's hospitals of Athens during the period October 1997 to October 1998. The isolates were further characterized by M-serotyping, examined for their susceptibility to penicillin, vancomycin and clindamycin, and categorized into resistance phenotypes. A total of 248 (21%) S. pyogenes isolates in the two main children's hospitals of Athens during the study period were resistant to erythromycin. All 49 EryR and 21 EryS isolates were susceptible to penicillin and vancomycin. With respect to erythromycin and clindamycin resistance, phenotypes M and IR MLSB dominated, with 30 and 17 isolates, respectively, two isolates belonged to the CR MLSB phenotype. Among the erythromycin resistant isolates, two M serotypes were dominant: M22 (30%) and M84 (41%). More specifically, M22 and M84 were most prevalent in resistance phenotypes IR MLSB (65%) and M (63%), respectively. In the susceptible group, no isolate belonged to these two M-serotypes, nor was a predominant serotype found. In contrast to susceptible isolates, two distinct M-serotypes were highly represented among EryR S. pyogenes isolates and predominantly associated with two distinct phenotypes.
Keywords: Anti-Bacterial Agents; Child; Clindamycin; Drug Resistance, Bacterial; Erythromycin; Greece; Humans; Streptococcal Infections; Streptococcus pyogenes